First record of the invasive bark beetle Polygraphus proximus Blandford (Coleoptera: Curculionidae, Scolytinae) in the Republic of Kazakhstan - Kirichenko, Natalia I.; Rudoi, Valentin V.; Efremenko, Anton A.; Petrov, Alexander V.; Baranchikov, Yuri N. (Altai State University, 2023)
The four-eyed fir bark beetle, Polygraphus proximus Blandford, 1894 (Coleoptera: Curculionidae, Scolytinae), is an aggressive invasive species originating from Far East. Over the past two decades, it distributed across Siberia, traversed the Urals and invaded some regions of the European part of Russia. In the secondary range, the pest kills heathy tree stands of Siberian fir, Abies sibirica Ledeb. (Pinaceae), both in native forests and man-made plantings, resulting in profound ecological and economic consequences. Here we report the first documented occurrence of this invasive pest in the Republic of Kazakhstan. Infested Siberian fir trees were discovered in the forest nearby Karaguzhikha village (East Kazakhstan Region), approximately 43 km away from Novoaleiskoye village (Altai Territory, Russia), where the pest was detected in 2016. The presence of trees colonized by the invasive pest and dead trees with specific symptoms in the examined forest stand suggest that P. proximus has likely been present in northeastern Kazakhstan for around a decade. The illustrations of affected habitat, male and female beetles and their morphological features are provided, and the early data on the damage caused by P. proximus and the potential for range expansions are discussed. The monitoring would be required to define the actual frontier of the pest distribution in Kazakhstan. Furthermore, it is imperative to alert the relevant authorities in Kazakhstan about the potential threat posed by this invasive tree-killer to native fir stands in the country.